A CASE OF ABDOMINAL INFLAMMATORY TUMOR DUE TO FISH BONE PENETRATION DIAGNOSED PREOPERATIVELY - KAI, Toshihiro; MIYATA, Michio; SHIINA, Yoshinao; TAKEMOTO, Nobuyuki; SEKIGUCHI, Katsuya; YAMAMOTO, Hiroshi; OKADA, Shinichiro (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2000)
A 69-year-old woman was seen at the hospital because of the left lower abdominal pain. An elastic hard mass with tenderness, approximately 10cm in diameter, was palpated on physical examination. White blood cell count was 10, 900/mm3 and CRP was 2.60mg/dl. Ultrasonography showed a hypoechoic and ill-defined mass connecting with the digestive tract. CT scan showed a low density mass with a linear calcification. An inflammatory tumor due to bowel penetration with a fish bone was strongly suspected based on a patient interview as well as findings of examinations. Barium enema study showed extrinsic pressure on both the left side of the transverse colon and sigmoid colon. At laparotomy, a tumor situating between the transverse colon and sigmoid colon was found. A partial colectomy including the tumor was performed. The resected tumor was yellowish-white in color containing puss and a fish bone of 2.5cm in diameter. When intraabdominal tumors of unknown origin are encountered, a possibility of some intestinal penetration with foreign body, such as a fish bones, should be considered. In making preoperative diagnosis, detailed patient interview and imaging diagnoses are also important.